Создание автоматизированного стенда для оцифровки данных с фотопленки - Баранчиков, Д. А.; Шандренко, Р. В.; Сорох, Н. О.; Антипов, И. Е. (ХНУРЭ, 2011)
Now scientists for calculations are increasingly using personal computers. To do this, it is very important to have data in digital format. Many years of research experience Automated Meteor radar recorded in the format of the film. For greater convenience, the film is required to translate it into digital format. In connection with this stand was set up to digitize the film. The task of the stand: digitize the maximum amount of data in the shortest period of time.
Keywords: следы метеоров; радиоволны метрового диапазона